Penerapan Media Flipbook untuk Meningkatkan Literasi Membaca Siswa SD - Lilik Binti Mirnawati; Regy Agatha Valent Fabriya (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
Indonesia is one of the countries in Asia with low reading literacy skills. Therefore, the mastery of reading literacy is vital for students and the Indonesian people. This study aims to describe the process of implementing flipbook media that can improve the reading literacy of 2nd graders of elementary school and measure the improvement of their reading literacy after the application of flipbook media. The method used is Classroom Action Research. The data collection uses observation techniques and documentation, and the literacy tests uses test sheets and documentation. The subjects of this research are 17 elementary school students in the 2nd grade of Muhammadiyah Elementary School 8 Surabaya. Based on the study results, the data show that flipbook media was applied online at the habituation stage and was carried out for 15 minutes before reading. The application of online-based flipbook media can improve students’ reading literacy and learning activities of the 2nd-grade students of Muhammadiyah Elementary School 8 Surabaya. The increase in reading literacy results can be seen in the literacy test results carried out in 2 learning cycles. Before applying flipbook, the result of classical literacy completeness was 29.41%. In the first cycle, the acquisition of classical reading literacy mastery was 47.06%, while in the second cycle, the classical completeness was 82.35%. So, it can be concluded that the use of flipbook media can improve the reading literacy of the 2nd-grade students of Muhammadiyah Elementary School 8 Surabaya